Camaldolesi e Vallombrosani nella Toscana medievale Repertorio delle comunità monastiche sorte tra XI e XV secolo - Fabbri, Antonella (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
In the context of the intense religious and social renewal known as "Gregorian Reform", the Camaldoli Hermitage and the Vallombrosa Abbey, both located in the Tuscan territory, gave rise to two movements of reform inspired by the spirituality of the respective founders, which later became congregations belonging to the benedictine family. Motivated by common instances, the Camaldolese and the Vallombrosan Orders were similar in some of their essential features and in the dynamics of their expansion. This statement has been the starting point of this work, which aims to formulate a comparative overview of the territorial spread of these reforms in Tuscany, by recording the known settlements and making an inventory of the religious communities interested by this phenomenom, in order to gather a broad range of examples of the way these movements interacted with the local situations in the different areas of the region. The text is enriched by a carthographic appendix illustrating the chronology of these congregations' development in medieval Tuscany.